Giovanni Domenico Santorini (1681–1737): A prominent physician and meticulous anatomist. Issue 4 (30th August 2013) - Kleinerman, Rachel; John, Alana; Etienne, Denzil; Turner, Benjamin; Shoja, Mohammadali M.; Tubbs, R. Shane; Loukas, Marios
<x xml:space="preserve">Abstract</x> Venetian physician Giovanni Domenico Santorini is revered as one of the most industrious and thorough anatomists of the eighteenth century. After receiving his medical degree in Pisa, Santorini worked as a physician and professor of anatomy and obstetrics in Venice. Of interest, he was a student of Malpighi while in Pisa. He quickly established himself as a dynamic lecturer and meticulous dissector. Santorini's anatomical observations include the prostatic venous plexus, accessory pancreatic duct, corniculate cartilage, parietal emissary veins, the risorius muscle, and many other structures. In addition to the detailed descriptions of these structures, he also produced copper plates and illustrations that are revered as "masterpieces" of that era. Santorini published Observationes anatomicae (Anatomical observations) in 1724, however his primary work, which included the description and anatomical drawings of the accessory pancreatic duct, was not published until thirty‐eight years after his death. This posthumous release of Jo. Dominici Santorini anatomici summi septedecim tabulae [Giovanni Domenici Santorini, the excellent anatomist's seventeen drawings] was accomplished by Giambattista Morgagni and his disciple, Michael Girardi in 1775. Giovanni Santorini's assiduous dissections have significantly enhanced our knowledge of human anatomy and his work has been immortalized with several anatomical eponyms. Clin. Anat. 545–547, 2014. © 2013 Wiley Periodicals, Inc.